2012
DOI: 10.1016/j.bbr.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between corticospinal excitability during motor imagery and motor imagery ability

Abstract: It is commonly reported that transcranial magnetic stimulation (TMS) of the motor cortex during action observation and motor imagery results in increases in the amplitude of motor evoked potentials (MEPs) in muscles specific to the observed or imagined action. This study aimed to determine whether MEP amplitude was related to the motor imagery ability of participants. Participants were 15 healthy, right-handed adults (5 male), with a mean age of 29.7 years. Motor imagery ability was measured using the Vividnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 32 publications
5
81
0
1
Order By: Relevance
“…Indeed, the time taken to imagine a movement correlates closely with subsequent execution times (Decety et al, 1989;Sirigu et al, 1996), with awkward and more physically demanding actions taking longer to imagine (Butson, Hyde, Steenbergen, & Williams, 2014;de Lange, Roelofs, & Toni, 2008;Munzert, Lorey, & Zentgraf, 2009). This relative functional equivalence is coupled with corresponding neurophysiological similarities, with neuroimaging studies indicating that imagined movements activate similar neural networks to those activated in actual movement (Jeannerod, 2001;Munzert et al, 2009) and corticospinal pathways (e.g., Williams, Pearce, Loporto, Morris, & Holmes, 2012). Consequently, it is largely assumed that MI provides insight into one's ability to accurately form and monitor the kinds of internal motor representations that support purposive action (de Lange et al, 2008;Jeannerod, 2001;Munzert et al, 2009).…”
Section: Development Of Online Controlmentioning
confidence: 97%
“…Indeed, the time taken to imagine a movement correlates closely with subsequent execution times (Decety et al, 1989;Sirigu et al, 1996), with awkward and more physically demanding actions taking longer to imagine (Butson, Hyde, Steenbergen, & Williams, 2014;de Lange, Roelofs, & Toni, 2008;Munzert, Lorey, & Zentgraf, 2009). This relative functional equivalence is coupled with corresponding neurophysiological similarities, with neuroimaging studies indicating that imagined movements activate similar neural networks to those activated in actual movement (Jeannerod, 2001;Munzert et al, 2009) and corticospinal pathways (e.g., Williams, Pearce, Loporto, Morris, & Holmes, 2012). Consequently, it is largely assumed that MI provides insight into one's ability to accurately form and monitor the kinds of internal motor representations that support purposive action (de Lange et al, 2008;Jeannerod, 2001;Munzert et al, 2009).…”
Section: Development Of Online Controlmentioning
confidence: 97%
“…With respect to the latter hypothesis, there is evidence that imagery ability mediates corticospinal activation during action observation. The amplitude of motor evoked potentials, as measured during transcranial magnetic stimulation of a finger-thumb opposition task, was found to be correlated with validated measures of imagery ability (Williams et al 2012). …”
Section: Imagery Observation and Action Simulationmentioning
confidence: 99%
“…A previous study reported that a gender difference was observed in brain activity during a mental rotation task [42]. Furthermore, since motor imagery ability would affect brain activity during motor imagery [46], we did not record motor imagery ability. In the future, we need to clarify whether effector-independent activity during motor imagery was different between male and female subjects or was affected by motor imagery ability.…”
Section: Limitationmentioning
confidence: 99%